Компьютерлік технологияларды меңгеру – бүгінгі білім берудің маңызды құрамдас бөлігі - Бұлақбаева, М.К.; Омашева, Н.Р. (My University, 2013)
In the article the problems of educating are examined in institution of higher learning in Message of president and use of computer technology in practice.